2006
DOI: 10.1291/hypres.29.857
|View full text |Cite
|
Sign up to set email alerts
|

Current Usage of Diuretics among Hypertensive Patients in Japan: The Japan Home versus Office Blood Pressure Measurement Evaluation (J-HOME) Study

Abstract: In the Japan Home versus Office Blood Pressure Measurement Evaluation (J-HOME) study, we examined the current situation with respect to the prescription of diuretics, including the prevalence of diuretic treatment and the dosages used for patients with essential hypertension in primary care settings. Of the 3,400 hypertensive patients included in the study, 315 (9.3%) patients (mean age: 66.9 ± 10.4 years; males: 43.5%) were prescribed diuretics. Compared with patients who were not using diuretics, those who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…When diuretics are used for combination therapy, low doses are generally employed considering both the antihypertensive effect and the metabolic effects. 23 In the COLM study, low doses of diuretics are being used, and we expect to obtain results that can also be achieved in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…When diuretics are used for combination therapy, low doses are generally employed considering both the antihypertensive effect and the metabolic effects. 23 In the COLM study, low doses of diuretics are being used, and we expect to obtain results that can also be achieved in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…When diuretics are used for combination therapy, low doses are generally used in consideration of both the antihypertensive effect and the metabolic effects. 29 Therefore, our study was designed to obtain results comparable to those achieved in clinical practice. Fourth, a potential limitation of the method used herein is that the calibration of central aortic pressure depends on the variability and inaccuracy of the oscillometric brachial pressure measurements required for radial waveform calibration.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in a previous study reported from Japan, many physicians used much dose of diuretics in clinical use. 21 In order to avoid metabolic side effects of diuretics, the steering committee of the COMFORT study, all members of which are Board Certified Member of The Japanese Society of Hypertension, considered that a small dose of a diuretic was appropriate to use for the combination therapy with an ARB.…”
Section: Discussionmentioning
confidence: 99%